Difficult septal deviation cases: open or closed technique? - Eliçora,Sultan Şevik (2017)
Abstract Introduction: The aim of this study is to compare the functional aspects of open technique (OTS) and endonasal septoplasty (ENS) in "difficult septal deviation cases". Methods: 60 patients with severe nasal obstruction from S-shaped deformities, multiple deformities, high deviations etc. were included in the study. The OTS was used in 30 patients and the ENS was performed in 30 patients. The Nasal Obstruction Symptom Evaluation (NOSE) scale was administered preoperatively and at first month following surgery. Patients were also evaluated for pain postoperatively with Visual Analog Scale (VAS). Results: The mean NOSE score was decreased 62.5-11.0 in the OTS group and 61.3-21.33 in the ENS group. Improvement of the symptoms following the two surgical techniques is similar and no statistically significant difference was found between both techniques. Also there was no statistically significant difference in postoperative pain between the OTS and ENS groups evaluated by VAS. Conclusion: ENS is as successful as the OTS in management difficult septal deviation cases. In patients with severe septal deformities type of the surgical technique should be selected according to the surgeon's experience and the patient's preference.